Physically Cross-Linked Gels of PVA with Natural Polymers as Matrices for Manuka Honey Release in Wound-Care Applications - Antonia Monica Neres Santos (Materials, 2019)
Manuka honey is a well-known natural material from New Zealand, considered to have properties beneficial for burn treatment. Gels created from polyvinyl alcohol (PVA) blended with natural polymers are potential burn-care dressings, combining biocompatibility with high fluid uptake. Controlled release of manuka honey from such materials is a possible strategy for improving burn healing. This work aimed to produce polyvinyl alcohol (PVA), PVA⁻sodium carboxymethylcellulose (PVA-CMC), PVA⁻gelatin (PVA-G), and PVA⁻starch (PVA-S) cryogels infused with honey and to characterize these materials physicochemically, morphologically, and thermally, followed by in vitro analysis of swelling capacity, degradation/weight loss, honey delivery kinetics, and possible activity against Staphylococcus aureus. The addition of honey to PVA led to many PVA crystals with defects, while PVA⁻starch⁻honey and PVA⁻sodium carboxymethylcellulose⁻honey (PVA-CMC-H) formed amorphous gels. PVA-CMC presented the highest swelling degree of all. PVA-CMC-H and PVA⁻gelatin⁻honey presented the highest swelling capacities of the honey-laden samples. Weight loss/degradation was significantly higher for samples containing honey. Layers submitted to more freeze⁻thawing cycles were less porous in SEM images. With the honey concentration used, samples did not inhibit S. aureus, but pure manuka honey was bactericidal and dilutions superior to 25% honey were bacteriostatic, indicating the need for higher concentrations to be more effective.